LEARNING AND CONTENTIOUS LEARNING: CRITICAL SUSTAINABILITY IN PEDAGOGY - Ryan Fernando; Elawati, Hendri Saut Parulian Simatupang, Ari Yono, Lela Octaria, Nova Lady Simanjuntak (CV. ADIBA AISHA AMIRA, 2023)
This paper discusses in depth the role played by psychology in the world of education and explores the benefits it offers. Educational psychology is a branch of psychology that focuses on understanding students' behavior and cognitive processes, and their influence on teaching and learning. This article tries to answer basic questions regarding how psychology influences the world of education in its various aspects.